Extent of Utilization of Social Networking Sites for Enhancing Academic Learning of Undergraduate Students in the South - South Nigerian Federal Universities - Johnbosco O.C. Okekeokosisi; Mary Noeleen Obi (University of Sofia, 2019)
The need for undergraduate students to utilize social networking sites for en-hancing their learning necessitated the study. The study was carried out to de-termine the extent of utilization of social networking sites (SNSs) for enhancing academic learning of undergraduate students. Five research questions and five null hypotheses guided the study. Proportionately stratified random sampling technique was used to draw the sample size of 331 undergraduate students from three out of the five federal universities in south-south geopolitical zone of Nigeria. A questionnaire titled the use of Social networking sites for Enhancing Academic learning of undergraduate students (USNSEAL-UGS) was developed by the researchers for data collection. The data were analyzed using mean, standard deviation and Z-test statistics. The findings from the results revealed that undergraduate students utilize Facebook, Whatsapp and Google+ for enhancing their academic learning at great extent. Gender had no influence on the undergraduate students' utilization of social network sites in enhancing their learning. Based on the findings, recommendations were made which include that seminars and workshops should be organized by donor agencies, philanthropists, management of tertiary institutions and student un-ion government (SUG) for undergraduate students in order to enlighten them on its effective utilization in improving their learning and their learning outcome.